Toxic Plants and Their Impact on Livestock Health and Economic Losses: A Comprehensive Review - Tagesu Abdisa; Tegegn Dilbato Dinbiso (Journal of Toxicology)
Plants are important components in sustaining the life of humans and animals, balancing ecosystems, providing animal feed and edible food for human consumption, and serving as sources of traditional and modern medicine. However, plants can be harmful to both animals and humans when ingested, leading to poisoning regardless of the quantity consumed. This presents significant risks to livestock health and can impede economic growth. In several developing countries, including Ethiopia, traditional communities have depended on medicinal plants for treating livestock and human diseases. The incidences of livestock poisoning from medicinal and poisonous plants are due to the misuse and lack of dosage standardization. Therefore, this paper aimed to review toxic plants and their effects on livestock health and associated economic losses. Toxic plants contain secondary metabolites that serve as a defense mechanism against predators. The most common secondary metabolites of toxic plants that affect livestock health and the economy include alkaloids (Asteraceae, Convolvulaceae, Lamiaceae, Fabaceae, and Boraginaceae), cyanides (Sorghum spp. and grass spp.), nitrates (Pennisetum purpureum roots, Amaranthus, nightshades, Solanum spp. Chenopodium spp., and weed spp.), oxalates (Poaecea, Amaranthaceae, and Polygonaceae), and glycosides (Pteridium aquiline). The most common effects of toxic plants on livestock health include teratogenic and abortifacient (Locoweeds, Lupines, Poison Hemlock, and Veratrum), hepatoxicity (Crotalaria, Lantana camara, Xanthium, and Senecio), photosensitization (L. camara, Alternanthera philoxeroides, Brachiaria brizantha, and Heracleum sphondylium), and impairing respiratory and circulatory systems (nitrite and cyanide toxic). Toxic plants lead to substantial economic losses, both direct and indirect. Direct losses stem from livestock deaths, abortions, decreased milk quality, and reduced skin and hide production, while indirect losses are associated with the costs of treatment and management of affected animals. Overall, toxic plants negatively impact livestock health and production, resulting in significant economic repercussions. Therefore, it is crucial to prioritize the identification of the most prevalent toxic plants, isolate secondary metabolites, conduct toxicity tests, standardize dosages, and develop effective strategies for managing both the toxic plants and their associated toxicity.